Examining Financial Anxiety Focusing on Interactions between Financial Knowledge and Financial Self-efficacy - Jae Min Lee; Abed Rabbani; Wookjae Heo (Journal of Financial Therapy, 2023)
This study examined whether the association between financial knowledge and financial anxiety depends on an individual’s financial self-efficacy by incorporating an interaction term between financial self-efficacy and financial knowledge. The self-efficacy component of the social cognitive theory of self-regulation has been tested using the 2018 National Financial Capability Study dataset. Households with higher financial knowledge and financial self-efficacy had lower levels of financial anxiety. After adding interaction terms of financial knowledge and financial self-efficacy in the model, the relationship between financial knowledge and financial anxiety depended on the levels of financial self-efficacy. Among those with anything less than high financial self-efficacy, the association between financial knowledge and financial anxiety weakens. The study found that financial knowledge and financial self-efficacy were significant in explaining financial anxiety and suggested implications for researchers, educators, and practitioners.
Keywords: Financial anxiety; Financial self-efficacy; Financial knowledge; National Financial Capability Study